Board independence and information asymmetry: family firms vs non-family firms. Issue 3 (18th October 2019) - Wu, Kean; Sorensen, Susan; Sun, Li
Abstract : Purpose: The purpose of this paper is to investigate the effect of independent directors in reducing firms' information asymmetry. Moreover, the authors enrich this investigation by differentiating the effectiveness of independent directors in an intriguing comparative setting of family vs non-family firms. Family firms are used to represent an interesting environment where controlling insiders (i.e. firms' founding families) have dominant control over corporate decisions. This study addresses the question of whether controlling-insiders dominate independent directors. Design/methodology/approach: The authors manually collect firms' founder information to identify family firm status in a sample of S&P 500 firms. Following a large literature in capital market research, the authors proxy information asymmetry by trading volume, bid-ask spread and price volatility. The authors employ multivariate regression with two-stage least square analysis, instrumental variable method, Heckman selection model and Hausman–Taylor model to address the issue of endogenous selection of board of director and family firm status. Findings: The authors find a negative relation between the board independence and information asymmetry, suggesting independent directors are effective in reducing information asymmetry. Furthermore, the authors find this negative relation is stronger in family firms. These results are robust after controlling for the endogenous issues using various models. Research limitations/implications: Our results suggest that independent directors in family-controlled firms are more successful in reducing information asymmetry than their counterparts in non-family firms. The authors provide direct evidence to support the existing theoretical arguments from Rediker and Seth (1995) and Anderson and Reeb (2004) that founding families and independent boards might be a powerful combination for aligning the interest of insider and diffused shareholders. The findings ease a prevalent concern that the role of independent directors might be compromised in an environment with controlling shareholders, and advocate regulations promoting board independence for various business practices. Originality/value: A number of studies concentrate on the practice of corporate disclosure of firm's performance and governance and how corporate disclosure mitigates information asymmetry (Leuz and Verrecchia, 2000 ;Ali et al., 2007 ;Chen et al., 2008 ). To the best of our knowledge, this study is the first to examine the impact of independent directors in reducing information asymmetry. The research adds to understanding the incentives of board members and supports recent findings that different types of investors have heterogeneous incentives for corporate disclosure (Srinidhi et al., 2014 ).